Functional link between mitochondria and Rnr3, the minor catalytic subunit of yeast ribonucleotide reductase - Isaac Corcoles-Saez; Jean-Luc Ferat; Michael Costanzo; Charles M. Boone; Rita S. Cha (Microbial Cell)
Ribonucleotide reductase (RNR) is an essential holoenzyme required for de novo synthesis of dNTPs. The Saccharomyces cerevisiae genome encodes for two catalytic subunits, Rnr1 and Rnr3. While Rnr1 is required for DNA replication and DNA damage repair, the function(s) of Rnr3 is unknown. Here, we show that carbon source, an essential nutrient, impacts Rnr1 and Rnr3 abundance: Non-fermentable carbon sources or limiting concentrations of glucose down regulate Rnr1 and induce Rnr3 expression. Oppositely, abundant glucose induces Rnr1 expression and down regulates Rnr3. The carbon source dependent regulation of Rnr3 is mediated by Mec1, the budding yeast ATM/ATR checkpoint response kinase. Unexpectedly, this regulation is independent of all currently known components of the Mec1 DNA damage response network, including Rad53, Dun1, and Tel1, implicating a novel Mec1 signalling axis. rnr3D leads to growth defects under respiratory conditions and rescues temperature sensitivity conferred by the absence of Tom6, a component of the mitochondrial TOM (translocase of outer membrane) complex responsible for mitochondrial protein import. Together, these results unveil involvement of Rnr3 in mitochondrial functions and Mec1 in mediating the carbon source dependent regulation of Rnr3.